Identifikasi Kelainan Gen Protein Pita 3 pada Membran Sel Darah Merah Penderita Talasemia β - Anna Maria Dewajanti (Jurnal Kedokteran Meditek, 2011)
Abstract : Thalassemia is a genetic disorder inherited as autosomal recessive. There is an imbalance Between the number of goblin chains α and b globin chains, so that there is an unpaired globin chains. Precipitation of unpaired globin chains in the membrane can lead to autooxidation the membrane so that it Can cause the cell membranes become rigid. Stability of red blood cell is very influenced by protein sitoskeleton function. Others the stability of red blood cells is also greatly influence by the band 3 protein, an integral transmembrane protein of red blood cells. Band 3 protein abnormalities may influence its function both as an ion exchange membrane  and in maintaining the stability of red blood cells. Abnormal band 3 protein found in ovalositosis, a blood di sorder caused by the loss of nine amino acids of protein band 3 due to a deletion of codons 400-408 in exon 11 band 3 protein gene. The loss of nine amino acids in the protein band 3 ovalositosis causes red blood cell membranes become rigid, thus reducing the membrane deformability. The existence of rigidity accompanied by a decreased ability of red blood cell membrane deformability thalassemia-like red blood cell membrane ovalositosis, raises the idea that the destruction of red blood cell membrane protein also thalassemia is caused by abnormalities band 3 protein-coding genes. This study aims to identify any abnormalities of band 3 protein gene in patients with thalassemia. Genomic DNA obtained from blood of healthy individuals and patients with thalassemia. Genes will be examined later propagated by PCR and visualization techniques using 2% agarose gel electrophoresis. PCR results of band 3 protein gene in healthy individuals (normal) size of 175 ± 25 bp, whereas in patients with thallasemia found two PCR product size 175 bp and 110 ± 25 ± 15 bp. Presence of PCR product size 110 ± 15 bp showed a protein  band 3 gene defects in patients with thalassemia in the form of gene deletion by 65 ± 10 bp. Genetic disorder of protein band 3 in thalassemia is not the same as genetic abnormalities in ovalositosis.Key words : thalassemia, protein band 3 gene, genetic disorders.